Technique for improving concrete characteristics with bacillus: Insights on strength and durability - Sayali Sandbhor; Sayali Apte; Shubham Puranik; Mansi Asati; Samyak Rai (MethodsX)
Numerous problems, including weathering, cracks, leaks, and bending, among others, appear in concrete after construction. The optimum procedure for treating concrete cracks is the subject of this study. The research goal is to find potential crack treatment materials and analyze the effect on the properties of concrete caused by the addition of bacterial solution to the concrete mix along with a particular method of preparation of bacterial solution. The principal results of the experimental testing showcased a successive growth in the compressive strength when the concrete cubes were casted with the bacterial addition from Bacillus family with a significant change in the quality of concrete. Following are the primary research outcomes of the method: • Use of Bacillus bacterial with direct addition in concrete improves concrete's performance. • The proposed method of concrete mix with Bacillus Sphaericus Solution in 30 ml concentration, replacing partial water cement ratio, yields maximum compressive strength on 28th day curing. For expediting setting time with high compressive strength, adding Bacillus Sphaericus solution in 45 ml concentration is recommended. • For achieving a homogenous mix with lesser cracks on 28th day, Bacillus Subtilis Spores in 30 ml concentration can be added to concrete with partial replacement of the water requirement.